Oral History Program Interview: William Rintoul - Rintoul, William
CALIFORNIA STATE COLLEGE, BAKERSFIELD CALIFORNIA ODYSSEY The 1930s Migration to the Southern San Joaquin Valley Oral History Program Interview Between INTERVIEWEE: William Rintoul PLACE OF BIRTH: Taft, Kern County California INTERVIEWER: Stacey Jagels